The Constructionist Role of Programming in the AI Era. Revisiting Seymour Papert’s Teaching Children Thinking from 1970: Evolution of Constructionism: Past, Present, and Future (Constructionism Conference Proceedings, 2025)
Long before constructionism had a name, Seymour Papert wrote about how a child could use a programming language to “learn to manipulate, to extend, to apply to projects, thereby gaining a greater and more articulate mastery of the world, a sense of the power of applied knowledge and a self-confidently realistic image of himself as an intellectual agent.” He described programming languages as opening “a vast universe of things to do. But the real magic comes when this is combined with the conceptual power of theoretical ideas associated with computation.” Here I argue that there is now another way to empower this kind of creativity and reflection. Constructionist learning can arise by conversing with a chatbot to build computer programs.